BASES OF STATE SUPPORT OF INNOVATIVE ENTREPRENEURSHIP - Iskakova Maral Serikovna,; Akhunova Dinara Ziyatovna, (Academic Journal of Physical and Chemical Sciences, 2020)
The problem, according to the authors, is that the development of a small innovative business is not facilitated by the complex and inadequate state system of regulation and support that is in need of entrepreneurs. The aim of the article is to study the operating conditions of small enterprises - participants of innovation clusters and the rationale for measures to improve government support aimed at realizing the innovative potential of small businesses. The methodological basis of the study is a systematic approach, methods of structural, subject, functional, statistical analysis, expert assessment method. The main directions of increasing the efficiency of state support of small innovative enterprises include: optimization of the regulatory framework, improving the evaluation of the activities of state programs and development institutions, providing patent support and protection of copyright, improving models of financing innovative activities. State support should be implemented taking into account the needs of a small innovative enterprise at the stages of the life cycle.